Kwestionariusz Reakcji Przystosowawczych (KRP) – polska adaptacja Reactions to Impairment and Disability Inventory – RIDI H. Livneha i R.F. Antonaka - Byra, Stanisława; Kirenko, Janusz (Studia Edukacyjne, 2020)
The paper presents Polish adaptation of Reactions to Impairment and Disability Inventory (RIDI), measurement scale developed by H. Livneh and R. F. Antonak, in Polish referred to as Kwestionariusz Reakcji Przystosowawczych (KRP) [Adaptive Responses Inventory Questionnaire]. It describes the conceptual grounds for the tool, stages of the adaptation process and psychometric properties of the scale. Based on the analysis of results of a study conducted on a group of 940 individuals with acquired disabilities (after spinal cord injury, lower extremity amputation or multiple sclerosis) and chronic illnesses (diabetes, cardiovascular diseases, cancer and rheumatoid arthritis), reliability, stability and accuracy of the questionnaire were verified. Results of the factor analysis provided grounds for selection of 8 factors – categories of adaptive responses, in accordance with the original scale. Conducted adaptation works have confirmed satisfactory psychometric properties of the questionnaire which may be used in Poland to diagnose various categories of non-adaptive and adaptive responses after suffering a deterioration of ability or development of a chronic illness.